Pure Immature Teratoma of the Ovary in Adults: Thirty-Year Experience of a Single Tertiary Care Center. Issue 9 (November 2015) - Alwazzan, Ahmad Bakr; Popowich, Shaundra; Dean, Erin; Robinson, Christine; Lotocki, Robert; Altman, Alon D.
Abstract : Objective: The aim of this study was to evaluate clinicopathologic characteristics, treatment outcome, and reproductive function in women diagnosed with ovarian immature teratoma (IT). Our standard chemotherapy regime is currently etoposide/cisplatin (EP), creating a unique opportunity to evaluate this protocol in ovarian ITs. Materials and Methods: This study is a retrospective analysis. Twenty-seven women older than 18 years with ovarian IT stages IA to IIIC were identified and included in this study. Patients were treated at 1 institution, Health Sciences Center, Women's Hospital, Winnipeg, Manitoba, Canada, between 1983 and 2013. Results: The median age at diagnosis was 27.0 years (range, 18–36 years). Twenty-two (82%) presented with an International Federation of Gynecology and Obstetrics stage I disease, 3 (11%) had stage II, and 2 patients (7%) had stage III disease. The histologic grade distribution was grade I in 9 patients (33%), grade II in 3 patients (11%), and grade III in 15 patients (56%). Initial management was surgical for all patients: 3 (11%) hysterectomy and bilateral salpingo-oophorectomy, 1 (4%) cystectomy only, and 23 (85%) unilateral salpingo-oophorectomy. Twenty-one patients (78%) received adjuvant therapy. The median follow-up was 60 months (range, 36–72 months). One patient recurred (histological grade III) 6 months after surgery and had a complete clinical response to 4 cycles of EP chemotherapy. Twelve patients reported an attempt to conceive resulting in 10 pregnancies (8 after chemotherapy). Conclusions: Ovarian IT is a curable disease. Fertility-sparing surgery should be offered. Adjuvant treatment with cisplatinum-based chemotherapy, typically with bleomycin, etoposide, and cisplatin, is still considered the standard in stages greater than stage IA grade I. Etoposide/cisplatin as a primary chemotherapy regime for early- or advanced-stage disease is an effective treatment with minimal adverse effects and high tolerability. This is the first published study examining EP as a primary treatment modality for IT. Further studies are needed to strengthen these findings.